Analisis Kedesipilinan Guru dan Peserta Masuk Kerja di SD GMIT 023 Ruilak - Gaudensius S. Yenifana; Jon A. Lalang Yame; Melki I. Puling Tang; Anelda S. Karta; Deviyanti Lekai; Agriyanti Momau; Aderika J. Peni (Pusat Riset dan Inovasi Nasional, 2024)
Discipline is one of the factors in successfully achieving learning goals. Disciplined teachers will have a positive impact on student development, so dedication and high responsibility are required. A teacher is required to be able to influence thought patterns, have broad insight, and must also have adequate competence, both in educational science, methodology, or the discipline that he will teach. The teaching profession is a noble profession, although it is sometimes looked down upon, it is very crucial in preparing the nation's next generation, who will continue the nation's leadership relay in the future. Teachers are also required to be able to provide good role models, so that they can produce generations that can be aspired to in the future. The benchmark for whether the condition of society is good or not is the world of education. Meanwhile, the main actors in the world of education are teachers, because teachers are the ones who will shape students to be good or bad. What society expects as a product of education from their children is their achievements, both academic and non-academic.According to Ulfatin and Triwiyanto (2016: 102), teacher discipline is a state of order and order that teachers have when working at school, without violations that are detrimental either directly or indirectly to themselves, their students and their colleagues.The research model used is the exponential model. The type of data used is primary data. Primary data is data taken through observation, interviews and documentation. Based on the results of student observations regarding the time discipline of both teachers and students, namely: 1. The culture of morning roll call which is held every day at Gmit 023 Ruilak Elementary School is 7.15 but based on observations of student teachers and students, not all of them are disciplined with time. Usually the teacher who arrives first on time is the teacher who has the task of leading the morning roll call while other teachers come. being late for school and not all of the students being there on time so that awareness of time discipline for both teachers and students is still very low.